Occupational exposure to flame retardants following production replacement and their effect on thyroid function indicators - Ling Meng; Tingting Guo; Yizhi Liu; Han Wu; Kang An; Xizhu Xu; Yuancheng Li (Emerging Contaminants)
With the ban of commercial Penta-BDEs, Octa-BDEs, and Deca-BDEs, many manufacturers have been transition to the production of novel brominated flame retardants (NBFRs), organophosphate ester flame retardants (OPFRs), and other alternatives. In this study, we recruited 165 employees with typical occupational exposure from a flame retardants (FRs) production plant in Laizhou Bay, which is the main FRs production area in China, to analyze the internal exposure characteristics of FRs and their potential impacts on thyroid function during the historical production and replacement process. The results showed that the detection frequencies of only triphenyl phosphate (TPHP), BDE-138 and BDE-197 (82.4 %, 61.2 % and 60.6 %, respectively) exceeded 60 % among the 34 compounds of interest, while the median concentrations of BDE-138 and BDE-197 were much higher than TPHP (medians of 103.6, 60.6 and 20.5 ng/g lw, respectively). In addition, the concentrations of these compounds in exposed group are higher than those in the control group (P < 0.05). The correlations among FRs indicated they mainly originated from the production and the debromination process. Overall, these results reflect the changes in the product structure. Free triiodothyronine (fT3) was moderately positively correlated with BDE-138, BDE-197, and TPHP (P < 0.05), and regression analysis further identified BDE-138 as a significant factor influencing fT3 levels. Despite TPHP having a rapid metabolism and short half-life, it was still widely detected in this study, indicating that future research should not only focus on the health risks of BDEs or their degradation products but also consider the health risks associated with TPHP and their mixed exposure, especially given the increasing production of OPFRs as substitutes.